Governance for tourism in rural areas. Monarch butterfly biosphere reserve - Esquivel Rios, Susana; Cruz Jiménez, Graciela; Zizumbo Villarreal, Lilia; Cadena Inostroza, Cecilia (Revista Mexicana de Ciencias Agrícolas, 2018)
Environmental impacts, including the loss of wild species and ecosystems; decrease in groundwater and soil erosion have become quite important in environmental public policies in Mexico. This, in direct consequence of the intense poverty and social exclusion in the communities and rural areas located within the so-called Protected Natural Areas (PNA), adoption product of economic policies, the lack of interest in some communities to conserve their resources and also for practicing mass tourism. In order to address this situation, in the context of environmental policy different ANPs were created in Mexico, including the Monarch Butterfly Biosphere Reserve (MBBR) and within this, 27 sanctuaries for protection. Most of them that make up the Corredor Chincua-Campanario-Chivati-Huacal, face a common problem: low productive investment, reduced local capacity to generate value added in the agricultural and forestry production and incipient development of industrial activities and services. The research on which this article is based on was developed from 2013, with the purpose of identifying the approach through public policy networks, the level of participation of the agents related to tourism in the corridor, to identify the governance setting in conservation and protection of natural resources and tourism development. We conclude that the complex network of agents difficult decisions, contributing to deepening social inequalities as well as causing serious conf licts in the governance process.
Keywords: conservation; monarch butterf ly; public policy; public policy networks